Dinamika Struktur-Agen dan Perubahan Internasional: Hegemoni AS vs World Polity pasca 911 - Lia Nihlah Najwah (Department of International Relations, Brawijaya University, 2015)
Abstract The primary aims of this writing are; First, to identify the dichotomy between reality and ideality, knowledge and power in international relations; second; to analyze contemporary global realitas. This research observed the growth of world polity after 911, especially after the global campaign of terrorism under Bush’ administration. The used method is kualitative research. The research which comes from theories and are used as the basic of analysis, phenomenon or facts which have the similarity or anomaly found out in some theories then, to observe the current changes in international politics. The analysis and the problem solving are delivered descriptively; the writer elaborated the thought and normative view of constructivism group about world polity and is confronted with the change of America’s hegemony after 911. The writer also added critics and another perspective of other thinkers to support the objectivity for this writing. Reflection of both idea and normative value to reality is the prime note which is used as a tool of analysis besides elaborate the concept of world polity. This writing conclude that: (1).World polity is not a single system, even though the breaking law is done by U.S, World polity has been differentiated and strong rooted in social international life. In other word, the action of U.S will not influence to the sustainability of world polity. Keywords: world polity, constructivim, social international life